Exploring the experiences related to postpartum changes: perspectives of mothers and healthcare providers in Iran - Mahboobeh Asadi; Mahnaz Noroozi; Mousa Alavi (BMC, 2021)
Abstract Background Numerous changes occur in different aspects of women's lives in the postpartum period. Women's adjusting with problems and taking advantage of this opportunity can develop their personality. In this regard, accurate knowledge of their experiences and feelings is necessary to help them to benefit from this period. Therefore, the present study aimed to explore the experiences related to postpartum changes in women. Methods In the present qualitative study, 23 participants, including women of childbearing age who gave birth and healthcare providers (midwives and obstetricians) in Isfahan, Iran were selected using purposive sampling with a maximum variation strategy. Data were collected through in-depth semi structured interviews, field notes, and daily notes, and simultaneously analyzed using the conventional qualitative content analysis. Results The data analysis results led to the extraction of three main categories including "feeling of decreased female attractiveness" (with two sub-categories of " feeling of decreased beauty" and "feeling of decreased sexual function"), "feeling of insolvency and helplessness" (with two sub-categories of "physical burnout", and "mental preoccupations") and "beginning a new period in life" (with three sub-categories of "changing the meaning of life", "feeling of maturity" and "deepening the communication"). Conclusions Findings of this study can provide a good context for designing interventions to improve the women's quality of life by explaining and highlighting their experiences in the postpartum period. In this regard, providing sufficient empathy, social and psychological support from family members (especially husband), performing appropriate educational interventions and also regular assessment of women's psychological state by healthcare providers in postpartum period can reduce their concerns and help to improve their health.